2-amino-1, 3-propanediol as a bioglycerol-derived solvent for CO2 capture / Nurul Fatin Nabilah Abdul Samat - Nurul Fatin Nabilah, Abdul Samat (2019)
In this work, aqueous 2-amino-1, 3-propanediol solution (serinol) was investigated as a potential solvent for CO2 capture. For this purpose, the solubility of CO2 in serinol were carried out at various concentration, pressure and temperature. Prior to CO2 solubility experiments, qualitative prediction using COSMO-RS approach based on quantum chemistry calculation was performed on serinol to confirm its potentiality as CO2 capture solvent. Based on this approach, serinol shows good affinity towards hydrogen ï¿½bond donors which is beneficial to develop intermolecular interaction between serinol and CO2. The solubility of CO2 in serinol were conducted at serinol molar concentration ranging from 1M to 3M, temperature ranging from 313.15 K to 353.15 K and CO2 pressures ranging from 1034.31 kPa to 2068.43 kPa. The solubility of CO2 achieved the highest value of 1.64 mol of CO2/mol of serinol in 1M serinol solution at 313.15 K and 2068.43kPa. The physical properties (densities and viscosities) of serinol at various concentration (1 - 3M), and temperature (298.15 - 333.15 K) were also conducted at atmospheric pressure. The results showed that the density and viscosity of serinol increase with increase in concentration and decrease in temperature. In addition, Henryï¿½s law constants of CO2 in serinol were calculated using N2O analogy due to the chemical reaction between the amine group in serinol and CO2. Henryï¿½s law constant were measured at temperature 313.15 K and 333.15 K for molar concentration 1M and 3M of serinol. The physical solubility of serinol increases as the temperature and the concentration of solution decreases. A 599.4 kPa.m3/kmol was the lowest Henryï¿½s law constant of CO2 for 1M of serinol at temperature of 313.15 K. Furthermore, the recyclability of 3M of serinol was carried out to investigate the stability of the solvent. The regeneration experiment was conducted at temperature of 313.15 K and partial pressure ranging from 1034.31 kPa to 2068.43 kPa. The maximum decreases of the regeneration efficiency after three regeneration cycles is 41.41%.